2022
DOI: 10.1093/pcmedi/pbac010
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunogenomic signature to predict prognosis and reveal immune infiltration characteristics in pancreatic ductal adenocarcinoma

Abstract: Background The immune response in the tumor microenvironment (TME) plays a crucial role in cancer progression and recurrence. We aimed to develop an immune-related gene (IRG) signature to improve prognostic predictive power and reveal immune infiltration characteristics of pancreatic ductal adenocarcinoma (PDAC). Methods The Cancer Genome Atlas (TCGA) PDAC was used to construct a prognostic model as a training cohort. Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…47 Abundant infiltration of CD3 + T cells and CD8 + T cells not only helps form a hot TME but also contributes to predicting ICB therapeutic efficacy. [48][49][50] Research also shows the crucial role of CD4+ T cells in the antitumor immune response, and their interaction with dendritic cells (DCs) is significant for stimulating cytotoxic T lymphocyte function. 51 Moreover, a recent study revealed that CD4 + T cells might reprogram the TME to a hotter TME by facilitating the normalization of tumor vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Abundant infiltration of CD3 + T cells and CD8 + T cells not only helps form a hot TME but also contributes to predicting ICB therapeutic efficacy. [48][49][50] Research also shows the crucial role of CD4+ T cells in the antitumor immune response, and their interaction with dendritic cells (DCs) is significant for stimulating cytotoxic T lymphocyte function. 51 Moreover, a recent study revealed that CD4 + T cells might reprogram the TME to a hotter TME by facilitating the normalization of tumor vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Effective antitumor immunity is mainly dependent on the orchestration of powerful T‐cell responses, and generally, CD3 and CD8 are identified as essential effectors of efficacy and representative of hot tumors 47 . Abundant infiltration of CD3 + T cells and CD8 + T cells not only helps form a hot TME but also contributes to predicting ICB therapeutic efficacy 48–50 . Research also shows the crucial role of CD4+ T cells in the antitumor immune response, and their interaction with dendritic cells (DCs) is significant for stimulating cytotoxic T lymphocyte function 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T cells target tumor cells that expose tumor-specific antigens in various malignancies, including pancreatic ductal adenocarcinoma [7,29,44] and higher CD8+ T-cell density in tumor is generally associated with prolonged pancreatic cancer survival [10,26,55,63]. Conversely, K17 has been associated with immune cell response in psoriasis as well as in basal cell skin cancer and in cervical carcinoma and is a negative prognostic biomarker in PDAC, suggesting that K17 might have some role in CD8+ T cell exclusion [60,66].…”
Section: K17 Has Profound Effects On the Pdac Immune Microenvironmentmentioning
confidence: 99%